Relight the Candle: What Happens to High-redshift Massive Quenched Galaxies - Rhea-Silvia Remus; Lucas C. Kimmig (The Astrophysical Journal)
A puzzling population of extremely massive quiescent galaxies at redshifts beyond z = 3 has recently been revealed by JWST and the Atacama Large Millimeter/submillimeter Array, some of them with stellar ages that show their quenching times to be as high as z = 6, while their stellar masses are already above 5 × 10 ^10 M _⊙ . These extremely massive yet quenched galaxies challenge our understanding of galaxy formation at the earliest stages. Using the hydrodynamical cosmological simulation suite Magneticum Pathfinder, we show that such massive quenched galaxies at high redshifts can be successfully reproduced with similar number densities as observed. The stellar masses, sizes, formation redshifts, and star formation histories of the simulated quenched galaxies match those determined with JWST. Following these quenched galaxies at z = 3.4 forward in time, we find 20% to be accreted onto a more massive structure by z = 2, and from the remaining 80% about 30% rejuvenate up to z = 2, another 30% stay quenched, and the remaining 40% rejuvenate on a very low level of star formation. Stars formed through rejuvenation are mostly formed on the outer regions of the galaxies, not in the centers. Furthermore, we demonstrate that the massive quenched galaxies do not reside in the most massive nodes of the cosmic web, but rather live in side nodes of approximately Milky Way halo mass. Even at z = 0, only about 10% end up in small-mass galaxy clusters, while most of the quenched galaxies at z = 3.4 end up in group-mass halos, with about 20% actually not even reaching 10 ^13 M _⊙ in halo mass.